Fucoidan Inhibits the Progression of Hepatocellular Carcinoma via Causing lncRNA LINC00261 Overexpression - Ma, Danhui; Wei, Jiayi; Chen, Sinuo; Wang, Heming; Ning, Liuxin; Luo, Shi-Hua; Liu, Chieh-Lun; Song, Guangqi; Yao, Qunyan (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) as a main type of primary liver cancers has become one of the most deadly tumors because of its high morbidity and poor prognosis. Fucoidan is a family of natural, heparin-like sulfated polysaccharides extracted from brown algae. It is not only a widely used as dietary supplement, but also participates in many biological activities, such as anti-oxidation, anti-inflammation and anti-tumor. However, the mechanism of fucoidan induced inhibition of HCC is elusive. In our study, we demonstrated that fucoidan contributes to inhibiting cell proliferation in vivo and in vitro, restraining cell motility and invasion and inducing cell cycle arrest and apoptosis. According to High-Throughput sequencing of long-non-coding RNAs (lncRNA) in MHCC-97H cells treated with 0.5 mg/mL fucoidan, we found that 56 and 49 lncRNAs were corresponding up- and down-regulated. Linc00261, which was related to the progression of tumor, was highly expressed in fucoidan treated MHCC-97H cells. Moreover, knocking down Linc00261 promoted cells proliferation by promoting the expression level of miR-522-3p, which further decreased the expression level of down-steamed SFRP2. Taken together, our results verified that fucoidan effectively inhibits the progression of HCC via causing lncRNA Linc00261 overexpression.